Tri-Center Educational Communication Strategies for Enhancing Public and Private Elementary School Branding in Yogyakarta - Alfina Bakti Pertiwi; Slamet Lestari; Mark Gabriel Wagan Aguilar (Universitas Muhammadiyah Surakarta, 2026)
This study was motivated by the declining public interest in public elementary schools alongside increasing trust in private institutions, highlighting the importance of communication strategies in shaping school branding and public trust. It aimed to analyze the implementation of the Tri-Center of Education communication strategy encompassing schools, families, and the community, and its impact on the branding of public and private elementary schools in Yogyakarta. A qualitative case study design was employed, involving two schools with distinct characteristics. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal that public schools emphasize institutional and structural communication, strengthening performance-based branding through academic achievement, professional governance, and institutional stability. In contrast, private schools adopt participatory and dialogical approaches, fostering value-based branding through religious identity, relational closeness, and positive emotional experiences. These findings underscore that integrated, sustainable, and socially grounded Tri-Center communication plays a crucial role in enhancing school branding and strengthening public trust.